Uji Kinerja Pompa Hidram dengan 1 Klep Buang dan 1 Klep Hisap Diameter 1 Inci - Kusuma, Abi Satria Jaya; Ridwan, Ridwan; Amien, Elhamida Rezkia; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2022)
Water is one of the most important factors for life, being a source of energy provided by nature as a mechanical power generator. Water supply, whether powered by electricity or diesel, has long been known by the villagers, but in reality, water shortages are one of the problems that are still being found. Use. Hydraulic Ram Pump (Hidram) is a very appropriate solution to be applied in rural areas, The advantage of the hydram pump can work without using fuel or additional energy from external sources, compared to other types of pumps that require additional energy from other sources or fuel, simple shape, easy to manufacture and maintain, and can work 24 hours per day To improve the performance of the hydraulic ram pump in this study, a study was conducted on the diameter of the intake and exhaust valves. The objectives of this research include finding the optimal 1 (inch) inlet height on the hydraulic ram pump assembly, finding the maximum (inch) hydram pump outlet height, the highest discharge and efficiency, knowing the energy flow of the hydraulic ram pump assembly system. The method used in this study is the technique of retrying (Trial and error), data collection is carried out by direct observation and measurement on the object of research. From the research that has been done, the hydraulic ram pump inlet discharge with a plunge height of 3 m has the highest value of 24.30 L/minute, the outlet discharge of a hydraulic ram pump with a pressure height of 4.5 m is the highest at a plunge height of 3 m, which is 3.91 L. /min, the calculated potential energy at the inlet pipe is 4.96 joules,19.81 joules, 44.43 joules. while the kinetic energy at the outlet pipe is 0.225x10-7joules, 0.3042x10-6joules, and 0.875x10-6joules.